Blockchain Identities: Notational Technologies for Control and Management of Abstracted Entities. - Dupont, Quinn (Metaphilosophy, 2017)
This paper argues that many so-called digital technologies can be construed as notational technologies, explored through the example of Monegraph, an art and digital asset management platform built on top of the blockchain system originally developed for the cryptocurrency bitcoin. As the paper characterizes it, a notational technology is the performance of syntactic notation within a field of reference, a technologized version of what Nelson Goodman called a 'notational system.' Notational technologies produce abstracted entities through positive and reliable, or constitutive, tests of socially acceptable meaning. Accordingly, this account deviates from typical narratives of blockchains (usually characterized as Turing or state machines), instead demonstrating that blockchain technologies are effective at managing digital assets because they produce abstracted identities through the performance of notation. Since notational technologies rely on configurations of socially acceptable meaning, this paper also provides a philosophical account of how blockchain technologies are socially embedded.